«Kurica ne ptica …» Demonologičeskaja ornitologija v krosskul'turnom prostranstveDemonološka ornitologija v medkulturnem prostoru - Belova, Olga; Petrukhin, Vladimir (Studia mythologica Slavica, 2007)
The article is devoted to the comparative analyses of mythological motifs spread in the folk Slavic and Jewish traditions and connected with the beliefs about the bird-like demons. The authors examine the legends and superstitions from the regions of close ethniccultural contacts, such as Western Ukraine, Western Belarus, and Poland, where the Slavic tradition had long-lasting interconnection with non-Slavic cultures. The aim of the investigation is to find parallels with the Slavic folklore evidences of bird features, which are attributed to some supernatural creatures in folk culture. In particular folk beliefs about the bird-legged demons, which can be identified by their footprints, may have their roots in the Talmud tradition. We can suppose that these motifs came to the Old Russia literature (treatises against the pagans) through the Byzantine mediation. As for the Ukrainian and Byelorussian folk beliefs about the bird-like demons, some of them could have been borrowed from the folklore of their neighbors – the Jews. This investigation was made in the framework of the research project “The Slavic Mythology: Results and Perspectives of Interdisciplinary Studies” supported by the Russian Foundation of Basic Research (grant 06-06-80095).